Organoid Technology: Current Standing and Future Perspectives. (30th September 2021) - Shariati, Laleh; Esmaeili, Yasaman; Haghjooy Javanmard, Shaghayegh; Bidram, Elham; Amini, Abbas
Abstract: Organoids are powerful systems to facilitate the study of individuals' disorders and personalized treatments. This emerging technology has improved the chance of translatability of drugs for preclinical therapies and mimicking of the complexity of organs, proposing numerous approaches for human disease modeling, tissue engineering, drug development, diagnosis, and regenerative medicine. In this review, we outline the history of organoid technology and summarize its faithful applications, and then we discuss the challenges and limitations encountered by three-dimensional organoids. Finally, we propose that human organoids offer a basic mechanistic infrastructure for "human modeling" systems to prescribe personalized medicines. : Organoid generation and therapeutic potential.